Pemikiran Fikih Abuya Muhammad Wali Al-Khalidi (Analisis Kitab Al-Fatawa) - Safriadi Saifuddin (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2020)
The Book of al-fatawa has a great contribution to the dynamics of development of Islamic law in this region of the Archipelago Islands. As for the complexion of his fikih thoughts nuanced bayāni-Tahlīlī. This research is descriptive-analysis with qualitative approaches. The results of this study revealed that Abuya Muhammad Waly al-Khalidi was a mujaddid (renewer) in the 14th-century hijrah, and a scholar was highly productive, during his lifetime preoccupied with scholarship activities with various disciplines, many of the wreaths he had made, which showed the breadth of science he had. One of his works in fikih is the book of al-Fatawa which is a collection of answers from questions sent by the community from various regions of Aceh as well as outside Aceh.